845. KINUGASA JAPONICA: Melanthiaceae. (September 2016) - Tamura, Minoru
Summary: Kinugasa is a monotypic genus of the family Melanthiaceae, consisting only of K. japonica, endemic to Japan. It grows in subalpine forests, often along the valleys where snow covers in winter, and is conspicuous by its large white or yellowish white petaloid outer tepals.